CONFORMITY OF MASCULINE NORMS AS A PREDICTOR OF NEGATIVE EMOTIONAL EXPRESSIONS AMONG THE CISGENDER MALE COLLEGE STUDENTS OF CEBU CITY - Crizza Joanne A. Mahinay, Engil Raimone M. Miano, Elisha Mel G. Sarausad, Maria Fe. F. Abejar (Chelonian Research Foundation, 2024)
Abstract – Men’s ability to express emotions is greatly influence by the crucial role of the norms of masculinity. The study aimed to determine whether conformity to masculine norms could predict negative emotional expression among the 250-cisgender engineering male students of Cebu City. Students who answered the Conformity to Masculine Norms – 46 (CMNI-46) and Negative Emotional Expressions (NES) were randomly selected. Descriptive analysis showed that majority of the students both had a moderate level of conformity to masculine norms and negative emotional expression of emotions. Predictive analysis revealed that conformity to masculine norms significantly predict negative emotional expressions (p = 0.033, r2 = 1.53%). Future research could explore on mediating factors that could give a more comprehensive understanding of the interplay between masculine norms and negative emotional expressions.